GE-14 in Johor : The Fall of the Fortress? - Hutchinson, Francis E. (Trends in Southeast Asia, 2019)
Johor is a key battleground in Malaysia's 14th General Elections. The state is economically vital to the country: it is the birthplace of the United Malays National Organization (UMNO); and it has a large number of parliamentary seats. Johor-specific dynamics that have worked to the advantage of the ruling coalition include: UMNO's unique links with the state; the tight control over religion; and the phenomenal scale and success of the Federal Land Development Authority (FELDA) scheme. Despite these advantages, support for the ruling coalition has been slipping across the state. Furthermore, the emergence of new parties such as Parti Pribumi Bersatu Malaysia (PPBM) will challenge Barisan Nasional's control over Johor's rural and Malay heartland. The redelineation of parliamentary and state constituencies now underway is however likely to benefit BN, and recent survey data indicate that Johoreans are yet to be attracted to the reconfigured opposition coalition, Pakatan Harapan. Thus, while BN may suffer a drop in support, it is likely to retain power in Johor.